2002
DOI: 10.1038/sj.bjp.0704497
|View full text |Cite
|
Sign up to set email alerts
|

Disparate effects of non‐steroidal anti‐inflammatory drugs on apoptosis in guinea‐pig gastric mucous cells: inhibition of basal apoptosis by diclofenac

Abstract: 1 Non-steroidal anti-in¯ammatory drugs (NSAIDs) induce apoptosis in gastrointestinal cancer cell lines. Similar actions on normal gastric epithelial cells could contribute to NSAID gastropathy. The present work therefore compared the actions of diclofenac, ibuprofen, indomethacin, and the cyclooxygenase-2 selective inhibitor, NS-398, on a primary culture of guinea-pig gastric mucous epithelial cells. 2 Cell number was assessed by staining with crystal violet. Apoptotic activity was determined by condensation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The role of diclofenac in apoptosis regulation has, however, been controversial. Even antiapoptotic effects have been attributed as suppression of ER stress-induced apoptosis in neuroblastoma cells (Yamazaki et al, 2006) and inhibition of basal apoptosis in guinea-pig gastric mucous cells (Ashton and Hanson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The role of diclofenac in apoptosis regulation has, however, been controversial. Even antiapoptotic effects have been attributed as suppression of ER stress-induced apoptosis in neuroblastoma cells (Yamazaki et al, 2006) and inhibition of basal apoptosis in guinea-pig gastric mucous cells (Ashton and Hanson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in rat liver cells, celecoxib and indomethacin stimulate the release of arachidonic acid, which may be associated with induction of apoptosis [27] . It has also been demonstrated that indomethacin and to some extent diclofenac cause apoptosis in chick embryo fi broblasts in a dose-and time-dependent manner [28] , whereas Ashton and Hanson [29] showed that diclofenac reduced the portion of apoptotic nuclei in guinea-pig gastric mucous cells. These studies in other tissues as well as the present study, indicate that the concentration is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the eye as well as in other tissues have found protective as well as damaging effects by NSAIDs/ASA [11,23,[31][32][33][34][35][36] . In a previous study, we found protection against hydrogen peroxide-induced apoptosis by NSAIDs/ASA at low concentrations, whereas higher concentrations were toxic, emphasizing the importance of the chosen concentration [23] .…”
Section: Discussionmentioning
confidence: 99%